REKONSTRUKSI HUKUM PUTUSNYA PERKAWINAN DALAM UNDANG-UNDANG PERKAWINAN - Ali Imron (Fakultas Hukum Universitas Wahid Hasyim, 2017)
Matrimonial law number 1 1974 is legal materil used as as a reference law in dispute resolution a marriage in court. The act of this out as evidence indonesian capable of engendering national legal products. The divorce in this law there is a difference in fundamental with fiqh munakahat or matrimonial law islamic.Hence must be founded a breakthrough law of reconstruction the results of dialectics law to stay puts forward unification national legal under a frame Pancasila. Reconstruction first, the receding judicial decisions on a limited extent that is divorce started after court decision has permanent legal power and effective as husband utter pledge thalak based on the court decision this court. Second , accommodate substance law materil fiqh munakahat about classifications thalak by adding a chapter namely if marriage breaking up because divorce , procedures divorce and effect law arranged according to law each religion and his trust. Key words: Islamic Law, Pancasila, Dialectics, National, Divorce